A Theoretical Study of Positively Curved Circulenes Embedded with Five-Membered Heterocycles: Structures and Inversions - Yijian Ma; Tianle Dai; Chengshuo Shen (Molecules)
Recently, polycyclic arenes with positive curvature have gained increasing significance in the field of material chemistry. This study specifically explores the inversion barriers of a series of positively curved circulenes by using five-membered heterocycles integrated into the backbone of primitive [5]circulenes and [6]circulenes. For hetero[5]circulenes, where one benzenoid ring is replaced by a heterocycle, the inversion barriers exhibit a strong correlation with the rotary angles of the heterocycles, and larger rotary angles result in lower inversion barriers. Additionally, the aromaticity of the circulene undergoes a significant reduction during the inversion process. As the number n of replaced rings increases, the inversion barriers can be adjusted, demonstrating an almost linear relationship with n. In the case of hetero[6]circulenes, molecules bearing heterocycles with small rotary angles also show positive curvatures. Furthermore, we examine the relationship between the radii of the fitted sphere for the circulenes and the inversion barriers, revealing an intriguing inverse proportionality between the fourth power of the radius and the inversion barrier. We anticipate that this research will offer a fresh perspective on studies related to positively curved polycyclic arenes.